Gambaran Pasca Trauma terhadap Perempuan yang Mengalami Kekerasan dalam Pacaran - Hali, Gandes Ramadhina Tuto; Lebuan, Adeline (Journal of Nursing Education and Practice, 2024)
Introduction: Dating violence is an act of someone who organizes, controls, manipulates, and commits acts of violence in the form of emotional and verbal, physical, sexual, and economic violence against their partner so that it has negative impacts such as trauma, crisis, and stress. Dating violence is experienced by the majority of women. Komnas Perempuan 2020 recorded 2,389 cases of dating violence. Someone who has gone through a traumatic period by experiencing positive changes is called Post-Traumatic Growth (PTG). Objectives: To find out the post-traumatic picture of women who experience dating violence. Method: This study used a purely descriptive design with a Probability Sampling approach, with Purposive Sampling of 91 respondents with the criteria of women who have been dating, and are not married. The data collection model is carried out using a questionnaire referring to the Likert scale. Data analysis in this study used univariate analysis and a series of statistical analyses with the help of the SPSS for Windows Program. Result: The results of the univariate analysis showed that the majority were 24.2% (22 people) aged 22 years, dating > 1 year were 58.2% (53 people), the majority of dating violence was in the mild violence category of 63.7% (58 people), and the majority of dating violence were in the severe category, namely emotional and verbal violence of 24.2% (22 people). The post-traumatic category was very low at 41.8% (38 people), and the majority of respondents who were able to overcome post-traumatic aspects, namely personal strength and appreciation in life, were 24.2% (22 people). Conclusion: The majority of respondents aged 22 years experienced dating violence <1 year and the post-traumatic category was very low, indicating that respondents experienced difficulties and needed time to heal from traumatic experiences. So it is necessary to provide counseling and coaching to adolescents in dating behavior.